2007
DOI: 10.1021/cm063047d
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Growth of PbTiO3 Nanoparticles into Microspheres and Bur-like Structures

Abstract: Novel bur-like hierarchical nanostructures of PbTiO3 were prepared by hydrothermal synthesis. Surfactants containing phenyl-sulfonic groups resulted in self-assembly of nanocrystals. In absence of the surfactant, monodisperse PbTiO3 microspheres were formed. The microspheres were 1−5 μm in diameter, and consisted of ∼20 nm tetragonal PbTiO3 crystals. The microspheres were formed by primary nucleation of PbTiO3 nanocrystals followed by aggregation into microspheres. The hierarchical bur-like nanostructures exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 26 publications
2
60
0
Order By: Relevance
“…This example very illustratively demonstrates the nanoparticle assembly process to a mesocrystal and its fusion to a single crystal as drawn in the corresponding schematics, [1,2] since in this example the building units are monodisperse. Other systems in which the time resolved mesocrystal to single crystal transition was observed include PbTiO 3 [128] or InOOH [129] where the transition to a single crystal is less documented and suggested to occur by dissolution-recrystallization of nanoparticle surfaces and/or removal of stabilizer molecules. [89,129] …”
Section: Mesocrystals As Intermediates In Single Crystal Formationmentioning
confidence: 99%
“…This example very illustratively demonstrates the nanoparticle assembly process to a mesocrystal and its fusion to a single crystal as drawn in the corresponding schematics, [1,2] since in this example the building units are monodisperse. Other systems in which the time resolved mesocrystal to single crystal transition was observed include PbTiO 3 [128] or InOOH [129] where the transition to a single crystal is less documented and suggested to occur by dissolution-recrystallization of nanoparticle surfaces and/or removal of stabilizer molecules. [89,129] …”
Section: Mesocrystals As Intermediates In Single Crystal Formationmentioning
confidence: 99%
“…Considering that the usually low initial coulombic efficiency (<70%) is one of the obstacles of commercialization of metal oxides, our results seem to give a way to solve this problem. Compared to other nanostructured iron oxides, the Fe 2 O 3 nanoparticle in our experiments are agglomerated into submicronparticles, which are significantly larger than the nanodomains and could result in reduction of the side effect with electrolyte [19]. On the other hand, loss of the active material during cycling may be also reduced by the relatively tight agglomerates.…”
Section: Resultsmentioning
confidence: 81%
“…However, it was reported that EG is very important for assembling the nanoparticles into aggregates. EG is expected to bind the nanoparticles together through eater bond formation after the aggregation has taken place [19]. The possible growth routine of submicron-size cube-like Fe 2 O 3 agglomerates is that nano-ellipses nucleate, grow and aggregate.…”
Section: Resultsmentioning
confidence: 99%
“…SDS affects the diffusion rate of various faces of the germanium dioxide and Ce germanate. The selective adsorption of SDS molecules on the surface of the crystalline nuclei induces the formation of the Ce doped germanium dioxide nanowires [20].…”
Section: Fig 2 Sem Images Of the Products Synthesized From 120mentioning
confidence: 99%